FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JERUK SIAM DI DESA BUNGA TANJUNG KECAMATAN BETARA KABUPATEN TANJUNG JABUNG BARAT - Wahyu Saputra, Muhammad; Aprollita, Aprollita; Lubis, Arsyad (Universitas Jambi, 2019)
This study aims to know: (1) The use of production factors at Orange Siam farm in Bunga Tanjung Village, Betara SubDistrict, Tanjung Jabung Barat District. (2) what factors influencing orange Siam production in Bunga Tanjung Village, Betara District, Tanjung Jabung Barat District. Sampling is done with Proportional Area Random Sampling Method. Analysis of the effect used is multiple linear regression with Ftest, Ttest, R2, and classical assumption test. the results of the analysis obtained value of R2 of 0.935, which means 93.5% change in the production variables orange Siam in Desa Bunga Tanjung can be explained by all independent variables used in the model. In t-test of variable of land area (X1) capital (X2), labor (X3) and farmer age (X4) have significant and significant effect to the production of Siam orange but the variable of labor (X3) is not significant. The classical assumption test states the distribution of normal data and does not occur multicolonierity, heteroscedasticity and autocorrelation. Based on this, the area of land (X1), capital (X2), labor (X3) and farmer age (X4) together have a significant effect on the production of Siamese oranges